1979
DOI: 10.1017/s0022029900017295
|View full text |Cite
|
Sign up to set email alerts
|

Sub-structure of synthetic casein micelles

Abstract: Casein micelles of different composition were synthesized in various ways and their sub-structure was investigated with the electron microscope by means of thin sections. Earlier studies of Schmidt et al. (1974) using the freeze-fracturing technique had shown no differences in the sub-structure of natural micelles and artificial micelles containing Ca and casein only. Contrary to these results our present studies showed that for the production of synthetic casein micelles with the same sub-structure as the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 2 publications
4
18
0
Order By: Relevance
“…Electron-dense areas, approximately 2-3 nm in diameter are visible inside the casein micelles (Fig. 2B), and this substructure probably originates from the presence of calcium phosphate clusters, as observed by others Knoop, Knoop, & Wiechen, 1979;Marchin et al, 2007). The surface structure of the casein micelles in untreated milk is somewhat rough and irregular, and the shape of the micelles does not appear perfectly spherical, which is in accordance with results from previous studies (Marchin et al, 2007;Martin et al, 2007).…”
Section: Resultssupporting
confidence: 90%
“…Electron-dense areas, approximately 2-3 nm in diameter are visible inside the casein micelles (Fig. 2B), and this substructure probably originates from the presence of calcium phosphate clusters, as observed by others Knoop, Knoop, & Wiechen, 1979;Marchin et al, 2007). The surface structure of the casein micelles in untreated milk is somewhat rough and irregular, and the shape of the micelles does not appear perfectly spherical, which is in accordance with results from previous studies (Marchin et al, 2007;Martin et al, 2007).…”
Section: Resultssupporting
confidence: 90%
“…The material in the pH range 4-6 to ~ 57 appears mostly homogeneous. The spherical particles showed a substructure, but not as pronounced as natural and artificial micelles which also contain phosphate and citrate (Schmidt et al 1974;Knoop et al 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Knoop et al 4 ) also suggested the importance of citrate in the casein micelle formation. They reported that the typical sub-structure of natural micelles was observed in an artificial casein micelle contammg citrate as well as calcium and phosphate by means of electron microscopy, whereas such a structure was not apparent in artificial casein micelles containing no citrate.…”
Section: Discussionmentioning
confidence: 99%